Bionomics, behaviour and control of the codling moth, Cydia pomonella (L.) (Lepidoptera: Tortricidae), in pome fruit orchards in South Africa - Blomefield, Thomas Loftus (Stellenbosch : Stellenbosch University, 2012)
Dissertation (PhD(Agric))--Stellenbosch University, 2003.